Jaw shape and mechanical advantage are indicative of diet in Mesozoic mammals - Nuria Melisa Morales-García (Nature Portfolio, 2021)
Nuria Melisa Morales-García et al. analyze jaw shape and mechanical advantage of 70 small modern mammals and 45 Mesozoic mammals and find that these metrics can be used to distinguish dietary groups for most extant mammals, and to infer diet in Mesozoic taxa.